2021
DOI: 10.1016/j.ejim.2021.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic interplay of kidney function with sarcopenia, anemia, disability and cognitive impairment. The GLISTEN study

Abstract: Background: Interactions between chronic kidney disease (CKD) and several comorbidities may potentially affect prognosis of older hospitalized patients. This study aims at evaluating the prognostic interactions between estimated glomerular filtration rate (eGFR), anemia, sarcopenia, functional and cognitive dysfunction, and 3year mortality among older patients discharged from acute care hospitals. Methods: Our series consisted of 504 older adults enrolled in a multicenter observational study carried out in twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Yoshimura et al also reported that the use of creatinine‐based eGFR in stroke patients showed an opposite reduction in the prevalence of sarcopenia as kidney function declined 22 . In addition, three previous studies showed that sarcopenia, particularly loss of muscle strength, was associated with increased mortality in patients with CKD 12,17,21 . One previous study incorporating 428 320 participants reported that participants with CKD and sarcopenia had a 33% higher hazard of mortality compared with those without (7% to 66%, P = 0.011), and that those with sarcopenia were twice as likely to develop end‐stage kidney disease (hazard ratio: 1.98; 1.45 to 2.70, P < 0.001).…”
Section: Kidney Function In Sarcopeniamentioning
confidence: 98%
See 2 more Smart Citations
“…Yoshimura et al also reported that the use of creatinine‐based eGFR in stroke patients showed an opposite reduction in the prevalence of sarcopenia as kidney function declined 22 . In addition, three previous studies showed that sarcopenia, particularly loss of muscle strength, was associated with increased mortality in patients with CKD 12,17,21 . One previous study incorporating 428 320 participants reported that participants with CKD and sarcopenia had a 33% higher hazard of mortality compared with those without (7% to 66%, P = 0.011), and that those with sarcopenia were twice as likely to develop end‐stage kidney disease (hazard ratio: 1.98; 1.45 to 2.70, P < 0.001).…”
Section: Kidney Function In Sarcopeniamentioning
confidence: 98%
“…Moreno‐Gonzalez et al reported that the prevalence of sarcopenia increases with more severe CKD when severity is classified using the formula, which estimates creatinine‐based eGFR, of the Berlin initiative study or the chronic kidney disease epidemiological collaboration 16 . Soraci et al reported that in elderly inpatients, those who died had a lower creatinine‐based eGFR and a higher prevalence of sarcopenia compared with those who survived 17 . Although these studies use eGFR based on serum creatinine, Groothof et al have suggested that creatinine‐based eGFR may be overestimated due to the muscle mass of the subjects 18 .…”
Section: Kidney Function In Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence gaps on the best strategies to adopt at specific stages of CKD are still present [ 1 , 4 , 5 , 6 ]. As a matter of fact, the stages of CKD, as proposed by Kidney Disease: Improving Global Outcomes (KDIGO) [ 4 , 7 , 8 ] are an important reference for clinical decisions and patients outcome in many cardiac diseases, both for medical and interventional treatments [ 9 , 10 , 11 ]. Catheter ablation with pulmonary veins isolation (PVI) is currently a valuable treatment option for applying a rhythm-control strategy to AF patients, and also as first-line treatment [ 2 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired physical performance [ 9 ], dependency in basic activities of daily living (BADL) [ 10 ], cognitive impairment [ 11 ] and malnutrition [ 12 ] are known to affect prognosis in older populations. In addition, aforementioned functional impairments may interact with kidney function to impact prognosis [ 13 , 14 ]. Thus, the influence of a geriatric assessment on the association between CKD stages and mortality is worth studying.…”
Section: Introductionmentioning
confidence: 99%